Fluorine Substitution in Magnesium Hydride as a Tool for Thermodynamic Control - Humphries, Terry; Yang, J.; Mole, R.A.; Paskevicius, Mark; Bird, Julianne; Rowles, Matthew; Tortoza, Mariana; Sofianos, M. Veronica; Yu, D.; Buckley, Craig (AMER CHEMICAL SOC, 2020)
© 2020 American Chemical Society.